Pengaruh Desain Kemasan Terhadap Persepsi Kualitas Produk, Nilai Produk Dan Preferensi Merek Pada Produk Susu Ultra Di Surabaya - Evelyn Griselda Hoisen (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This study aims to determine the effect of packaging design on perceived quality, packaging design on brand preference, perceived quality on product value, product value on brand preference and perceived quality on brand preference. The type of research used is quantitative research and the sampling technique is purposive sampling technique with the number of samples obtained based on criteria and data analysis techniques using SEM Amos. This research was conducted by distributing questionnaires through as many as 150 respondents. The results showed that packaging design had a significant positive effect on perceived quality on Ultra Milk consumers, packaging design had no effect on brand preferences on Ultra Milk consumers, perceived quality had a significant positive effect on perceived value on Ultra Milk consumers, perceived quality had a significant positive effect on brand preferences on consumers of Ultra Milk and perceived value has a significant positive effect on brand preference for consumers of Ultra Milk.